2017
DOI: 10.1038/s41598-017-02703-2
|View full text |Cite|
|
Sign up to set email alerts
|

Thickness-dependent Crack Propagation in Uniaxially Strained Conducting Graphene Oxide Films on Flexible Substrates

Abstract: We demonstrate that crack propagation in uniaxially strained reduced graphene oxide (rGO) films is substantially dependent on the film thickness, for films in the sub-micron regime. rGO film on flexible polydimethylsiloxane (PDMS) substrate develop quasi-periodic cracks upon application of strain. The crack density and crack width follow contrasting trends as film thickness is increased and the results are described in terms of a sequential cracking model. Further, these cracks also have a tendency to relax wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…S1, small drop spacing and thicker films can induce microcracks with higher density and larger crack openings upon strain. This higher sensitivity to deformation leads eventually to a higher gauge factor, as also observed in [49] in reduced graphene oxide.…”
Section: Resultsmentioning
confidence: 56%
“…S1, small drop spacing and thicker films can induce microcracks with higher density and larger crack openings upon strain. This higher sensitivity to deformation leads eventually to a higher gauge factor, as also observed in [49] in reduced graphene oxide.…”
Section: Resultsmentioning
confidence: 56%
“…Finite element simulations showed that the substrate delocalizes the strain, so that the metal film can be extended indefinitely, limited only by rupture of the polymer substrate [ 182 ]. However, a discrepancy between experiment and theory may arise due to the influence of the very small particle size and inadequate interfacial adhesion [ 183 ]. Since debonding plays an important role in this failure mechanism, an adhesive layer that improves adhesion between the film and substrate causes strain localization and cracking of the copper film.…”
Section: Structural Designs For Flexible Sensory Systemsmentioning
confidence: 99%
“…This condition is caused by the thermal coefficient difference between two or more materials. The stress in the films is highly dependent on annealing temperature, thickness, and chemical contents [34][35][36]. Besides, the different transmittances may be due to the various morphologies, shapes, defect states, and sizes as well as porous structures when varying the number of NiO layers on  -Fe2O3 structures [37].…”
Section: Transmittance and Absorbancementioning
confidence: 99%